A STUDY ON BIOMEDICAL WASTE DISPOSAL MANAGEMENT IN A MULTISPECIALTY HOSPITAL - Dr. Ritesh P. Kundap, Dr. Saptarishi Bose (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background Biomedical waste generated in healthcare settings poses significant risks topublic health and the environment if not managed properly. Effective biomedical wastemanagement is essential to prevent disease transmission and environmental contamination.This study aims to evaluate